Analisis Strategi Pemasaran UMKM Toko Buah Dalam Menghadapi Persaingan Pasar - Dian Lovenia; Jamaludin Jamaludin; Lilis Renfiana (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Fruit is one of the foods that many enjoy adequately because of their good taste and have many health benefits, such as rich in vitamins and other nutrients. The fruit market flourished because so many communities were attracted to the fruit. Fruit sellers competed closely with one another in the market as the fruit trade flourished. Each fruit merchant has a different business plan to boost sales in his or her store in the face of this tough competition. Companies that produce goods or services can gain a competitive advantage that is sustained by applying marketing strategies. One of the pillars underlying a comprehensive business plan is the marketing plan. Because of the mostly fierce competition umkm faces, these businesses need to have a marketing plan to fight the competition. The purpose of this study is to know and evaluate marketing strategies and to improve competitiveness. The research was done on the ayu sulastri and amri's fruit shop. A technique used for data collection with observation, interviews, and documentation. In the sulastri stores each year increases, in the last year up 21%. Whereas at the amri store, income increases by 2023 from 2020 to 2023 begins to increase little by little and by 2023 gets an increase by 11%. The results of research on the marketing strategy found increases in the year but there was a decline in the year. Keywords: Marketing Strategy, UMKM, Market Competition